ChemInform Abstract: Perfluorocyclohexene Bridges in Inverse DiArylEthenes: Synthesis Through Pd‐Catalyzed C—H Bond Activation, Experimental and Theoretical Studies on Their Photoreactivity. Issue 51 (17th December 2013) - Yuan, Kedong; Boixel, Julien; Le Bozec, Hubert; Boucekkine, Abdou; Doucet, Henri; Guerchais, Veronique; Jacquemin, Denis
Abstract The title reaction affords a new family of 1, 2‐di(heteroaryl)perfluorocyclohexenes such as (III) and (V).